(untitled) (Research, Society and Development, 2021)
Introduction: In 2018, the International Cancer Research Agency (IARC), estimated the rate of new cancer cases at 18.1 million and 9.6 million deaths from the disease for the same year. There is a worldwide estimate of 29.5 million new cases for the year 2040. Methodology: This is a descriptive study, of the type of experience report, elaborated from the experience of nursing residents of a Multiprofessional Residency Program in Health developed in a unit of high complexity in oncology of a university hospital located in the state of Piauí. Results and discussion: Knowing about the diagnosed disease and its treatment, generates comfort that reduces anxieties, fears and sadness and improves the way in which conflicts are managed by the patient. The nurse must pass security to the person with oncological disease, involve the patient in all stages of care and provide relevant guidance on the process. Final considerations: In view of this, it is possible to infer that with the study a new look was obtained about the possibilities of care in oncology, and in addition, added technical and scientific knowledge, indispensable for clinical practice.